2023
DOI: 10.1155/2023/2198259
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Risk Factors for Aspiration in Patients Hospitalized with Community-Acquired Pneumonia

Abstract: Background. Aspiration pneumonia (AP) is difficult to diagnose and has poor outcomes. This case-control study aimed to explore the risk factors and delineate the antibiotic usage for AP. Methods. Inpatients diagnosed with community-acquired pneumonia (CAP) from 2013 to 2017, enrolled in the urban employee basic medical insurance program in Beijing, were included and classified into the AP (N = 2,885) and non-AP (N = 53,825) groups. Risk factors were identified by logistic regression. Results. Older age (compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Age was one of the risk factors for aspiration. With the increase of age, the functions of each organ of the body shows different degrees of physiological decline, especially the re ex function and swallowing function [33]. Moreover, elderly patients are often complicated with a variety of internal medical diseases such as cardiovascular and cerebrovascular diseases and pulmonary diseases, so age becomes an important cause of aspiration [34].…”
Section: Discussionmentioning
confidence: 99%
“…Age was one of the risk factors for aspiration. With the increase of age, the functions of each organ of the body shows different degrees of physiological decline, especially the re ex function and swallowing function [33]. Moreover, elderly patients are often complicated with a variety of internal medical diseases such as cardiovascular and cerebrovascular diseases and pulmonary diseases, so age becomes an important cause of aspiration [34].…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that patients with AP were more inclined to be older and to have a higher prevalence of different underlying conditions, particularly diabetes mellitus, chronic heart disease, and cerebrovascular disease, which was generally consistent with previous reports. 18 , 22 The integrity of the oropharyngeal sensory system is essential for maintaining swallowing function. With the increase of age and underlying diseases, pharyngeal sensitivity and swallowing reactivity impaired, the protective reflex of epiglottis and glottis reduced, especially in the setting of cerebrovascular diseases, the swallowing function and cough reflex impaired, leading to an increased risk of AP.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 AspRF includes advanced age, male, dysphagia, head and neck cancer, upper gastrointestinal disease, reduced conscious level, degenerative neurologic diseases (parkinsonism, dementia, and multiple sclerosis), chronic obstructive pulmonary disease, alcohol dependence, and sedative drug abuse. 2,3,18 AspRF-CAP was defined as CAP patients with AspRF. 3,9 A total of 94 patients with CAP from three hospitals were eligible for screening (Figure 1).…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…However, VE requires highly experienced staff and is somewhat invasive to the patient. In addition to these three phases, cognitive and masticatory functions must be assessed to achieve feeding without aspiration [18,19]. Cognitive function contributes to the recognition of the size or hardness of food and movement of the appropriate amount of food into the oral cavity.…”
Section: Discussionmentioning
confidence: 99%